The silver lining of red tape - Ronald B. Davies (University College Dublin, UCD School of Economics, 2010)
An increasing number of international agreements require nondiscrimination from their participants, i.e. the government of one country cannot treat foreign firms differently from domestic firms. This is at odds with a government's desire to benefit its own citizens rather than foreign citizens. I show that the use of red tape - a wasteful application process - can achieve de-facto discrimination. Key to this result is firm heterogeneity since, although the red tape cost is constant across firms, only those sufficiently benefiting from an incentive program will find it worth the cost of applying. If the benefits of targeting subsidies outweigh the burden of red tape on domestic firms, red tape will be used.
hdl:10197/2652
Keywords: H2; F2; 330; Red tape; Firm heterogeneity; Production subsidies; Discrimination